Unique composition and evolutionary histories of large low velocity provinces - James Panton; J. Huw Davies; Paula Koelemeijer; Robert Myhill; Jeroen Ritsema (Scientific Reports)
Abstract The two “large low velocity provinces” (LLVPs) are broad, low seismic wave speed anomalies in Earth’s lower mantle beneath Africa and the Pacific Ocean. Recent research suggests they contain relatively dense subducted oceanic crust (SOC), but the relative concentration of this recycled material within them is an open question. Using simulations of 3-D global mantle circulation over the past 1 Gyr, we find that two antipodal LLVPs develop naturally as a consequence of Earth’s recent subduction history and the gravitational settling and stirring of SOC. Shear-wave velocity reductions in the two LLVPs are similar due to the dominating influence of temperature over composition. However, the formation histories are distinct. Circum-Pacific subduction of oceanic lithosphere has continuously replenished the Pacific LLVP with relatively young SOC since 300 Ma, while the African LLVP comprises older, well-mixed material. Our models suggest the Pacific LLVP stores up to 53% more SOC produced in the last 1.2 Gyr than the African LLVP, potentially making the Pacific domain denser and less buoyant.